HUBUNGAN KUALITAS LAYANAN ANTENATAL CARE DENGAN KEPUASAN PASIEN DI PUSKESMAS II PURWOKERTO UTARA - Etika Dewi Cahyaningrum; Safitri Damayantii (Universitas Harapan Bangsa Purwokerto, 2012)
Background :The quality of maternal health services in Indonesia is still belowexpectations. Compliance with health care facilities to the standard of service isstill need to be improved and enhanced. Antenatal care is health care by healthprofessionals (obstetricians and midwives, general practitioners, midwives andnurses) to pregnant women during pregnancy. Factors influencing antenatalvisits, among others: the knowledge of pregnant women, health center facilities,and the satisfaction derived.Target of :The purpose of this study was to determine the relationship betweenthe quality of antenatal care with patient satisfaction.Method :This type of research is a kind of analytic survey research with crosssectional approach. The population in this study were all pregnant women whohad antenatal care at the health center II North Purwokerto, Banyumas Regency.The sampling method used is incidental sampling, were 40 respondents. Methodsof data collection using questionnaires.Result of :Patient assessment of quality of ANC services at the health center IINorth Purwokerto, Banyumas regency in 2012, mostly in the category of eitheragree or as many as 25 respondents (62.5%). To the satisfaction of patients at thehealth center II North Purwokerto, the majority of respondents in the categorysatisfying as many as 29 respondents (72.5%). Based on the results of Spearmanrank test, the value of Ï value 0,001 <Î± (0.05), then there is a strong relationshipbetween the quality of antenatal care with patient satisfaction in the health centerII North Purwokerto, Banyumas Regency Year 2012 (CC = 0.622).Conclusion :There is a strong relationship between the quality of antenatal carewith patient satisfaction in the health center II North Purwokerto, Banyumasregency. Keyword :Quality of care, antenatal care, patient satisfaction